Cs1−xDMAxPbI3 versus CsPbI3 for Perovskite Solar Cells. Issue 7 (31st January 2023) - Liu, Mengqi; Duan, Linrui; Jacobsson, T. Jesper; Luo, Jingshan
Abstract : Inorganic CsPbI3 perovskite solar cells (CsPbI3 PSCs) have attracted extensive attention because of their excellent thermal stability and appropriate bandgap for tandem solar cells. At present, intermediate phase engineering with organic additive, e.g., dimethyl amine iodide (DMAI), is the most common method to obtain high‐efficiency CsPbI3 PSCs. However, it remains controversial whether the intermediate phase is entirely converted into a pure CsPbI3 phase. By exploring the effect of annealing temperature, herein, it is demonstrated that substantial organic residues remain in the produced films while using the current standard recipes of DMA + ‐assisted synthesis of Cs1− x DMA x PbI3 perovskites. Thermal gravimetric and nuclear magnetic resonance show that DMA + remains in films annealed at a standard annealing temperature of 190 °C. The DMA + does, however, disappear if the annealing temperature is increased to 340 °C, which leads to a larger grain size, a contraction of the lattice, a narrower bandgap, and a redshift of the absorption onset. Though both Cs1− x DMA x PbI3 and CsPbI3 perovskite solar cells show decent efficiencies, the pure CsPbI3 perovskite solar cells annealed at a higher temperature demonstrate higher operational stability. Abstract : In the fabrication of inorganic γ‐CsPbI3 perovskite solar cells with dimethylamine iodide as an additive, annealing at low temperature (≈190 °C) won't completely remove the DMA, Cs1− x DMA x PbI3 is thus formed, but phase‐pure CsPbI3 samples can be obtained by further annealing at high temperatures (≈340 °C). Both compositions show decent efficiencies for solar cell application, but the pure CsPbI3 device demonstrates higher stability.